Jejak antikolonial kesusastraan Balai Pustaka dalam novel Sitti Nurbaya: Kasih Tak Sampai - Tjaraka, Ajeng Rahayu; Tjahjandari, Lily (Universitas Mulawarman, 2024)
In the creation of literary works, the author will always be influenced by the spirit of the times (Zeitgeist) that existed during the writing process. Sitti Nurbaya: Kasih Tak Sampai, a novel by Marah Rusli, is one of the literary works that is close to Minangkabau culture. It was first published in 1922 by Balai Pustaka. Balai Pustaka established strict regulations in publishing reading materials for people in the Dutch East Indies to stem the nationalism of indigenous peoples. This research aims to find the strategies used by Marah Rusli to convey the anticolonial discourse contained in the work. The method used in this study is a qualitative descriptive method with the sociology of literature approach and Stuart Hall’s concept of representation. The results that the researcher found in this study are the anticolonial traces conveyed by Marah Rusli using various strategies to escape the censorship of Balai Pustaka, namely (1) the construction of youth figures representing the modernity of the Dutch colonial government and the elderly representing the traditionality of indigenous people; (2) the portrayal of anticolonial attitudes through antagonistic characters; and (3) the use of the year of Hijri to deceive the Dutch colonial government.